Retraction Note: Improving usability and pregnancy rates of a fertility monitor by an additional mobile application: results of a retrospective efficacy study of Daysy and DaysyView app - Martin C. Koch; Johannes Lermann; Niels van de Roemer; Simone K. Renner; Stefanie Burghaus; Janina Hackl; Ralf Dittrich; Sven Kehl; Patricia G. Oppelt; Thomas Hildebrandt; Caroline C. Hack; Uwe G. Pöhls; et al. (BMC, 2019)
.